Use Of Interactive Methods In Activating Students’ Cognitive Activity In The Conditions Of The Credit Module System Of Higher Education - Alimova Zulfiya Karimovna (Genius Journals, 2025)
This article extensively discusses the introduction of the credit-module system in the higher education system of Uzbekistan and its impact on the educational process, methods of activating students’ cognitive activity, and theoretical and practical aspects of using interactive teaching methods. Since the credit-module system requires the development of students’ independent learning skills, interactive methods are becoming an integral part of the educational process.
Keywords: Independent learning; competence; interactive methods; credit module